The Quantification of Chinese Society: Why Did Liang Qichao Ask for Statistics? - Christ, Stefan (Journal of the European Association for Chinese Studies, 2025)
This article seeks to explain the sharply increasing tendency to quantify Chinese society in the twentieth century. It argues that this trend is inherently connected to the passage from a hierarchically stratified society to a one that was more functionally differentiated, which also resulted in the emergence of a new concept of society. The relation between social differentiation and quantification is explored by way of comparing an eighteenth-century essay by Qian Weicheng, which presents a rather typical late imperial vision of social order, with an early twentieth-century article by Liang Qichao, which is one of the earliest texts to lament the lack of numbers and statistics regarding the Chinese populatio